2017
DOI: 10.21873/anticanres.12085
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Inhibition of Human Carcinoma Cell Growth via Co-Delivery of p53 Plasmid DNA and bcl-2 Antisense Oligodeoxyribonucleotide by Cholic Acid-modified Polyethylenimine

Abstract: The co-delivery of p53 plasmid DNA and bcl-2 AS ODN in PEI-CA complexes enhanced therapeutic activities of both p53 plasmid DNA and bcl-2 AS ODN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In study by Weecharangsan et al, PEI was used as a co-delivery system for a plasmid constructed with gene-targeted therapy or small interfering RNA (siRNA). 35 The findings indicated that the use of this system could reduce toxicity in normal cells, increase the efficiency of gene transfection, and enhance the inhibition of cancer cells. In vitro analysis showed that the combination of PEI with siRNA could increase the efficiency of gene transfection and reduce toxicity in normal cells.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…In study by Weecharangsan et al, PEI was used as a co-delivery system for a plasmid constructed with gene-targeted therapy or small interfering RNA (siRNA). 35 The findings indicated that the use of this system could reduce toxicity in normal cells, increase the efficiency of gene transfection, and enhance the inhibition of cancer cells. In vitro analysis showed that the combination of PEI with siRNA could increase the efficiency of gene transfection and reduce toxicity in normal cells.…”
Section: Methodsmentioning
confidence: 98%
“… DR5-positive (cervical cancer, liver cancer, prostate cancer) HeLa, HepG2, and NIH 3T - [ 34 ] 6. Branched, 25 kDa - pEGFP, Bcl-2 AS ODN PEI-CA/pEGFP and Bcl-2 AS ODN PEI-CA complexed with Bcl-2 AS-ODN and pEGFP plasmid Cervical cancer HeLa - [ 35 ] 7. Linear, 22, 87, and 217 kDa Branched, 25 kDa - pZsGreen1-N1 PEI/pDNA Bovine fetal fibroblast, kidney cancer, liver cancer BFF, HEK293, and HepG2 - [ 36 ] 8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, a CA modified polyethylenimine (PEI-CA) polymer was developed for the synergistic inhibition of human carcinoma cell growth. 90 Interestingly, the results indicated that PEI-CA inhibited the cellular growth via codelivery of both plasmid DNA P53 and bcl-2 antisense oligodeoxyribonucleotide (AS ODN) in HeLa cells. It also displayed low toxicity and performed extraordinarily throughout gene transfection.…”
Section: Cholic Acid-based Polymers For Therapeutic Applicationsmentioning
confidence: 99%
“…With the help of a number of in vivo and in vitro experiments, they addressed the fact that the synthesized polymeric conjugate had high potency for achieving targeted colorectal delivery of DOX and siRNA. Later on, a CA modified polyethylenimine (PEI-CA) polymer was developed for the synergistic inhibition of human carcinoma cell growth . Interestingly, the results indicated that PEI-CA inhibited the cellular growth via codelivery of both plasmid DNA P53 and bcl-2 antisense oligodeoxyribonucleotide (AS ODN) in HeLa cells.…”
Section: Cholic Acid-based Polymers For Therapeutic Applicationsmentioning
confidence: 99%